2023
DOI: 10.12968/bjon.2023.32.6.s28
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stoma management education on the self-care abilities of individuals with an intestinal stoma

Abstract: An intestinal stoma is a surgically formed exteriorisation of the large or small bowel on to the anterior abdomen wall, to enable faeces to be excreted from the body. Patients living with a stoma may encounter physical, psychological, and social barriers and challenges. Stoma self-management education is essential to improving self-care competence, and patients who perceive the benefits of self-management education show a better adjustment to living with a stoma. This literature review explored the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Many patients are not able to manage their ostomy themselves, mostly due to a lack of education on ostomy self-care [3,5]. This often results in the need for ostomy care by visiting nurse services [6,7].Educational plans have been proven effective to improve knowledge and self-care and, based on two systematic reviews, seem to be applicable to ostomy patients as well and result in improved quality of life [8][9][10]. It has been reported that only a few educational sessions during admission would be sufficient to provide patients with ostomy care skills [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients are not able to manage their ostomy themselves, mostly due to a lack of education on ostomy self-care [3,5]. This often results in the need for ostomy care by visiting nurse services [6,7].Educational plans have been proven effective to improve knowledge and self-care and, based on two systematic reviews, seem to be applicable to ostomy patients as well and result in improved quality of life [8][9][10]. It has been reported that only a few educational sessions during admission would be sufficient to provide patients with ostomy care skills [10].…”
mentioning
confidence: 99%
“…This often results in the need for ostomy care by visiting nurse services [6,7].Educational plans have been proven effective to improve knowledge and self-care and, based on two systematic reviews, seem to be applicable to ostomy patients as well and result in improved quality of life [8][9][10]. It has been reported that only a few educational sessions during admission would be sufficient to provide patients with ostomy care skills [10]. This was also observed in a recent study by van Loon et al [11], which described that a 4-day in-hospital…”
mentioning
confidence: 99%
See 1 more Smart Citation